RANCANGAN JIG DAN FIXTURE PEMBUATAN PRODUK COVER ON-OFF - Hendro Prassetiyo; Rispianda Rispianda; Haris Adanda (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
The manufacturing industry has been growing rapidly at this time, it can be seen from the number of manufacturing companies that have emerged and growing. Obstacles often occur over production activity in a manufacturing company is a long setup times and product quality in production activities which will indirectly affect the output product to be produced. The longer of the setup activities will result in the output of products which are getting smaller. Improved product quality and minimize setup time can be done either by the use of tools manufacturing which is often known as jigs and fixtures. This paper will discuss the design of jig and fixture for manufacture products cover on-off. Jigs and fixtures are designed to be used for the process drilling for three holes. Jig and Fixture design results can provide a reduction in total time of manufacture of the product, product quality improvements, increased productivity and cost saving product manufacture for products cover on-off.